2017
DOI: 10.1002/14651858.cd012638.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Oral nonsteroidal anti-inflammatory drugs (NSAIDs) for cancer pain in adults

Abstract: There is no high-quality evidence to support or refute the use of NSAIDs alone or in combination with opioids for the three steps of the three-step WHO cancer pain ladder. There is very low-quality evidence that some people with moderate or severe cancer pain can obtain substantial levels of benefit within one or two weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 111 publications
(17 reference statements)
2
37
0
5
Order By: Relevance
“…However, there are reports stating that chronic aspirin consumption lowered PSA levels in patients by 5-10% at the time of PCa diagnosis, compared with patients that did not take aspirin (25,27,29). To the best of our knowledge, the mechanism by which aspirin decreases PSA levels at the time of diagnosis has not yet been determined, nor has whether that effect is associated with disease progression (56)(57)(58). Notably, in the present clinical trial, mefenamic acid was demonstrated to decrease PSA levels when administered to patients with CRD-PCa.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reports stating that chronic aspirin consumption lowered PSA levels in patients by 5-10% at the time of PCa diagnosis, compared with patients that did not take aspirin (25,27,29). To the best of our knowledge, the mechanism by which aspirin decreases PSA levels at the time of diagnosis has not yet been determined, nor has whether that effect is associated with disease progression (56)(57)(58). Notably, in the present clinical trial, mefenamic acid was demonstrated to decrease PSA levels when administered to patients with CRD-PCa.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no sufficient evidence of the included records about reducing cancer-related pain in children and adolescents (72) , and no high-quality evidence to support the use of NSAIDs alone or in combination with opioids for the three step WHO cancer pain ladder (73) .…”
Section: Research Hotspotsmentioning
confidence: 99%
“…2 The role of NSAIDs in cancer pain was assessed in a recent Cochrane review. 6 Nine of the 11 included studies had substantial risk of bias, being small and having incomplete outcome data. In four studies, NSAIDS initially reduced moderate or severe pain after 1 or 2 weeks (415 participants).…”
Section: Non-steroidal Anti-infl Ammatory Drugsmentioning
confidence: 99%